Changes in GPS-Derived Community Mobility After Motor Skill Training in Older Adults. (17th December 2021) - Crane, Breanna; Moored, Kyle; Carlson, Michelle; Perera, Subashan; Brach, Jennifer; Klatt, Brooke; Rosso, Andrea; Dunlap, Pamela
Abstract: The study purpose was to identify the effects of a motor skill training intervention to improve gait speed on community mobility among community-dwelling older adults. The study included 249 participants randomized to standard physical therapy or a standard plus motor skill training program. Community mobility was measured using the Life Space Assessment (LSA) and GPS at baseline, 12 (post-intervention), 24 and 36 weeks. There were 124 participants (M age=77.4±6.7; 68.6% female; LSA: 76.2±17.6) randomized to the standard plus and 125 (M age=77.4±6.4; 62.4% female; LSA: 74.3±18.2) to the standard group. There was no significant between-group difference in pre- or post-intervention LSA scores and no significant pre- to post-intervention change over time in either group. GPS results are pending. While there were no differences in self-reported LSA, we anticipate objective GPS measurement of community mobility will better capture post-intervention changes and differences between groups.